Industrialised Building System (IBS) adoption in Iran, perception of users and industry participants - Ashrafi, Mohammad Sharif (Kulliyyah of Architecture and Environmental Design, International islamic University Malaysia, 2017)
The Iran government has brought the Industrialized Building System (IBS) to the interest of all professionals in the construction industry. Due to certain barriers, the actual project of the IBS implementation could not be achieved. One of the factors recognized is the lack of customer gratification with IBS houses. This research aims at (i) finding out the factors pertaining to customer gratification of IBS houses and (ii) to determine IBS adoption factors for Iranian construction industry. The research objectives are to improve customer gratification with IBS houses and to develop strategies for IBS adoption in the Iranian construction industry. This research uses a mixed-method methodology. The research was conducted in three (3) phases of data collection. The respondents were divided into two (2) groups i.e. the IBS house occupiers and the construction industry participants. The quantitative method was based on a self-administered questionnaire survey. Data were obtained from eighty-two (82) IBS house occupiers to determine customer gratification in the first phase. Data from twenty-five (25) valid respondents from construction participants were also obtained to determine the IBS adoption factors in the second part of the first phase survey. Focus group discussion was adopted under qualitative method for the second and third phase of the research. From the overall analysis of customer gratification level, it was found that 70.7% respondents were satisfied, and 4.9% were very satisfied. Overall gratification level of IBS construction participants shows that the majority of the respondents are satisfied, and 4% of the respondents are very satisfied. List of strategies on how to improve customer gratification on IBS house progress and strategies on how to improve the IBS adoption in the Iran construction industry were developed. IBS house occupiers gratification was analysed using expressive analysis from the quantitative study. To determine IBS adoption factors, a statistical analysis was conducted to prove the reliability of the instruments used. Findings of the study exposed nine (9) customer gratification factors related to IBS house construction as well as nine (9) factors were identified as the critical factors in IBS adoption in the final phase of the research.